PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT. ONIC SINAR SANJAYA JAKARTA BARAT - Marselino Marselino; Mohamad Duddy Dinantara (Al Hasanah Barokah Foundation, 2025)
This study aims to determine whether the Work Environment and Job Stress have an effect on the Employee Performance of PT Onic Sinar Sanjaya West Jakarta, to determine whether the Work Environment has an effect on the Employee Performance of PT Onic Sinar Sanjaya West Jakarta. To determine whether Job Stress has an effect on the Employee Performance of PT Onic Sinar Sanjaya West Jakarta. The methode used in this study is a quantitative methode, with a saturated sampel determination obtained by 61 respondents. The data used through observation techniques, questionnaires and literature. The analysis methods used in this study are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, multiple linear regression test, determination test and significance test (t test and f test). The results of the study showed that the Work Environment partially had a significant effect on Employee Performance, as evidenced by the t-test results with a calculated t-value of 5.183 ≥ 2.002. Partially, Job Stress did not have a positive and significant effect on Employee Performance, as evidenced by the t-test results with a calculated t-value of 1.938 ≤ 2.002. Simultaneously, the Work Environment and Job Stress had a significant effect on Employee Performance, as evidenced by the F-test results with a calculated F-value of 14.886 ≥ 2.760. Multiple linear regression obtained Y = 17.915 + 0.388 X1 + 0.145 X2 with an adjusted R-square coefficient of determination of 0.339 or 33.90%.